Multifocal pleural capillary hemangioma: a rare cause of hemorrhagic pleural effusion-case report - Naifu Nie; Zhulin Liu; Jun Kang; Li Li; Guoqiang Cao (BMC Pulmonary Medicine, 2021)
Abstract Background Capillary hemangioma can be found in many organs, but rarely in pleura. Previously, only localized pleural capillary hemangioma cases have been reported. Corticosteroids are the most commonly recommended drugs in capillary hemangioma. Case presentation Here, we present a case of a young woman with recurrent hemorrhagic pleural effusion. Despite repeatedly thoracentesis, the routine examinations, including chest computed tomography (CT) scan, pleural effusion biochemical test, and cytology all failed to make a definite diagnosis. Thus, single port video-assisted thoracoscopy (VATS) was then performed. Numerous nodules arising from the parietal pleura were found, and biopsies showed multifocal pleural capillary. However, recurrent pleural effusion was successfully managed by oral azathioprine, after failure of dexamethasone treatment. Conclusions To our knowledge, this is the first case of a patient with recurrent hemorrhagic pleural effusion masquerading as malignant pleurisy, but in fact caused by multifocal pleural capillary hemangioma.